The Roll of Artificial Intelligence in Teaching Pedagogy: Challenges and Prospects for Sustainable Growth in Education - Gomathi, R D; Maheswaran, S; Sathesh, S; Murugesan, G; Duraisamy, Prakash; Nandita, S; Karthik, R P (2022 13th International Conference on Computing Communication and Networking Technologies (ICCCNT), 2022)
All the youngsters, nowadays, are not keen to developing their knowledge. Moreover, the students are easily addicted to mobile phones. So, the performance level decreases and reduces their thinking ability as well technology has grown, all the answers are now available in the internet. If they search since the internet, they get their answers directly but without knowing the base from how it came. Therefore, everyone is trying to reach the upcoming technologies without strong in their basics. Hence, a model is created with the help of toolkit (like courseware, etc.) where the technology behind this is AI. This toolkit (packaged to use with computers) comes up with different subjects (subjects were designed based on the year of study). After a concept is thought to an individual or if a concept is learned individually, this toolkit works as a tester and gives the performance and feedback on the level of their understanding. On analyzing the results, the perspective of each individual is identified. The data is passed to ANN, each level of students is happened and the metrics have shown an efficiency of 94.3%. The result produced for each individual is given to an AI model. According to the perspective of each individual, automatic questions are generated by the AI model to increase their level of knowledge and the way of thinking. It helps every individual to be strong in their concepts and no need for searching the answers for every question. Therefore, it is understood that the proposed model has higher efficiency 95% in training the students and teaching the concepts as well.